Blockchain Adoption as a Pathway to AI Intention: A Toe-Based Moderated Mediation Model with Green Technology Orientation in the Indonesian Oil and Gas Industry - Sihombing, Maruahal; Syairudin, Bambang; Asy’ari, Muhammad Khamim (International Review of Management and Marketing, 2026)
Digital transformation in capital-intensive regulated industries proceeds through sequential capability accumulation rather than simultaneous technology deployment, yet the organizational mechanisms governing this sequentiality remain theoretically underspecified. This study examines whether blockchain adoption mediates the relationship between Technology-Organization-Environment (TOE) factors and artificial intelligence adoption intention, and whether green technology orientation moderates this mediation pathway, within the Indonesian oil and gas industry. Drawing on absorptive capacity theory and the TOE framework, a moderated mediation model was tested using PLS-SEM on cross-sectional survey data from 350 decision-makers across upstream, midstream, and downstream oil and gas firms operating under SKK Migas governance. Results establish that environmental factors constitute the singular significant TOE driver of blockchain adoption, while technology and organizational factors yield non-significant effects a pattern attributable to the quasi-mandatory institutional adoption logic governing Indonesia's petroleum sector. Blockchain adoption subsequently exerts a strong positive effect on AI intention, confirming a sequential capability-building mechanism consistent with absorptive capacity theory. Green technology orientation both directly predicts AI intention and significantly amplifies the blockchain AI intention pathway, functioning as a strategic interpretation filter rather than an independent adoption antecedent. These findings advance TOE theory by specifying boundary conditions under which internal adoption determinants lose predictive salience, extend absorptive capacity theory into sequential digital technology domains, and introduce sustainability orientation as a configurational moderator with direct relevance for energy firms confronting simultaneous digital transformation and decarbonization imperatives.